Trend in women representation among authors of high rank rheumatology journals articles, 2002–2019. (9th February 2021) - Levinsky, Yoel; Vardi, Yoav; Gafner, Michal; Cohen, Neta; Mimouni, Michael; Scheuerman, Oded; Furst, Daniel E; Amarilyo, Gil
Abstract: Objective: The representation of women among authors of peer reviewed scientific papers is gradually increasing. The aims of this study were to examine the trend of the proportion of women among authors in the field of rheumatology during the last two decades. Methods: Articles published in journals ranked in the top quartile of the field of rheumatology in the years 2002–2019 were analysed. The authorship positions of all authors, country of the article's source and manuscript type were retrieved by specifically designed software. Results: Overall, 153 856 author names were included in the final analysis. Of them, 55 608 (36.1%) were women. There was a significant rise in the percentage of women authors over time ( r  = 0.979, P  <0.001) from 30.9% in 2002 to 41.2% in 2018, with a slight decline to 39.8% in 2019. There were significantly fewer women in the senior author positions compared with the first author positions (24.3% in senior position vs 40.9% as first author, P  <0.001). Conclusion: The proportion of women among authors of rheumatology articles has increased over the years, both in general and as a first or senior author; however, their proportion is still <50% and there is still a gap between the proportion of women among first authors and the proportion of women among senior authors.